THE PHENOMENON OF CONTAGIOUS FINANCIAL BUBBLES - E. B. Netunaev (Финансы: теория и практика)
Topic. The author examines the phenomenon of contagious financial bubble — a situation in which a financial bubble arises on the stock market of one country as a result of events on the stock market of another country. Globalization of financial markets has created the conditions for the migration of financial bubbles from one market to another. As a result, to the classical causes of investors’ euphoria, such as economic growth and credit expansion, it is necessary to add the activity of foreign investors.Purpose. The purpose of this paper is a determination of measures to counter infectious bubbles.Methodology. Based on comparative analysis of theoretical and empirical papers we identified the infectious mechanisms of formation of financial bubbles. We conducted statistical analysis of financial bubbles in the US and China. The analysis considered the dollar index family MSCI: they are calculated by one source, based on a common methodology that allows avoiding distortions due to the different construction principles of indices. Also, we conducted a detailed study of the phenomenon of co-integration stock markets.Results. The article highlights the basic mechanisms of contagious financial bubbles. Based on the comparison of financial bubbles in the US and China we showed that infectious bubbles are formed under the influence of the situation on the financial markets of developed countries. Further, we determined the conditions of infection of financial bubbles. In accordance with the results of the analysis of the causes and mechanisms of occurrence of contagious bubbles, we discussed possible measures of control for the prevention of financial bubbles. Summarizing the results obtained, we identified priority measures to counter infectious bubbles.Conclusions. Efforts to curb financial bubbles (including through measures of monetary policy) are seen as ineffective. It is preferable to take measures to contain the negative consequences of the collapse of prices in consequence of the collapse of financial bubbles.